What can Portugal learn from Ireland and to a less extent from Greece? An empirical approach searching for the sources of growth - Catarina Cardoso; Elias Soukiazis (European Regional Science Association (ERSA), 2004)
The present paper focuses on the analysis of growth sources in Portugal, Greece and Ireland explaining the differences in economic performance between these three countries which constitute the “cohesion group” in the EU. During the nineties, Ireland has made a remarkable economic recovery, converging rapidly to the richest countries of the EU, while Portugal converged at a very modest rate. Greece is a peculiar example of having great difficulties of adaptation at the early years of its integration and only recently (since 1999) revealed signs of recovery in contrast to the slowdown of economic activity in Portugal. This raises the questions why was Ireland able to grow faster, which were the causes of its faster growth, and what can Portugal learn from the Irish success in economic improvement and the recent recovery of the Greek economy. This paper tries to shed light to these questions and to identify the main sources which drove economic growth in the three countries. Our evidence shows that differences in productivity levels, capital accumulation in human resources and technology, foreign direct investment and most of all export capacity are the main factors explaining differences in economic performance between these three countries. Keywords: per capita income, productivity, export-led growth, foreign trade elasticities and error correction models.
Keywords: 330; per capita income; productivity; export-led growth; foreign trade elasticities and error correction models